INCLUSIVE LEADERSHIP AND EMPLOYEE PERFORMANCE IN RELIGIOUS OFFICES - Reijeng Tabara (LPPM Politeknik Saint Paul Sorong, 2023)
The purpose of this study was to determine the effect of Inclusive Leadership on the performance of employees at the Sorong district Religious Office. This research uses Partial Least Squares (PLS) with Structural Equation Modeling (SEM) technique to analyze 91 employees. The results showed that there was a positive and significant effect of Inclusive Leadership on employee performance with a Tstatistic value greater than Ttable (Tstatistic 19.711 > Ttable 1.96) at a significance level of 5% (0.05). The results of this study indicate that the higher the Inclusive Leadership, the higher the performance of employees at the Religious Office of Sorong district, West Papua